Estudo parametrizado da teoria escalar-tensor-vetor da gravidade - Pereira, Marcos Henrique Novaes (2023)
The Scalar Tensor Vector theory of Gravity by Moffat, also known as MOG (Modified Gravity), constitutes an alternative theory aiming to explain the dynamics of galaxies and clusters without the need to invoke the concept of dark matter. In a weak field approximation, the theory modifies the Newtonian law of attraction through a Yukawa repulsive force. As such, MOG has shown efficacy in appropriately reproducing galaxy rotation curves and in major tests within the solar system. However, there’s a disagreement concerning the value of the parameter γ, associated with light deflection and Shapiro delay. In this scenario, this current work aims to study the weak field and low-speed limits of MOG through a second-order extension of the parametrized post-Newtonian (PPN) formalism. Thus, we reviewed previous versions and found γΣ ≈ 1.0432. The parameter was also assessed considering a scenario where the Newtonian limit is not a requirement.